GE_GERICHTE P/15185/2024 vom 27. August 2024 - GE Cour de justice (2024)
QUALITÉ POUR AGIR ET RECOURIR;LÉSÉ;MORT;PARTIE À LA PROCÉDURE;ORDONNANCE DE NON-ENTRÉE EN MATIÈRE | CPP.115; CP.173; CP.181; CPP.382; CP.110; CPP.121; CPP.310